KELAYAKAN LEMBAR KERJA PESERTA DIDIK SUBMATERI ORGAN TUMBUHAN KELAS XI SMA - Fiqri, Muhammad Ahlil; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aim to determine the feasibility of Student Worksheets for sub material structure and function of plants tissue in class XI high school. The Student worksheet conten was called plant organ adapted from the biology book by Irnanigtiyas. Student worksheet component refered from Depdiknas modification consisting of titles, learning instructions, objectives, supporting information, work step and assignments, and assessment. The research was descriptive research, student worksheet was validated based on aspects of content, language, presentation, and graphics. Learning materials for student worksheet were are validated by 5 validators. The results of  five validators for student worksheet plant organ obtained the value Content Validity Index (CVI) of 0.925. Based on Lawshe calculations with five validators CVI value ranging from 0-1 included in valid category. Thus the student worksheet of plant organ categorized valid, which means it is feasible to be used as teaching material in the sub material plant organs in class XI high school. Keywords:  feasibility, student worksheet, plant organs